Integrated removal of chromium, lead, and cadmium using nano-zero-valent iron-supported biochar: Mechanistic insights and eco-toxicity assessment - Yuzhen Wei; Jialu Yu; Fasih Ullah Haider; Qinhu Zhang; Run Chu; Cai Liqun (Ecotoxicology and Environmental Safety)
The contamination of water and soil by heavy metals (HMs) is a global issue that should be given much more concern. Modified nano-zero-valent iron (nZVI) composites offer an effective strategy for HMs remediation, but few studies have focused on removing coexisting HMs and the eco-toxicity of the composite. In this study, corn straw biochar-supported nZVI composites (nZVI-BC) were synthesized, characterized and used for the removal of Cr6 +, Pb2+, and Cd2+ in single and multi-system at different composites dosages, metal concentrations, and solution pH. This study indicated that the composites exhibited enhanced removal capacities for Cr6+, Pb2+, and Cd2+ (respectively 82.24, 737.2, and 545.28 mg g−1), which were considerably superior to those observed with the sole application of biochar (0.05, 89.88, and 108.49 mg g−1) and nZVI (39.8, 297.35, and 191.02 mg g−1). Results of the remediation application of the composites to multi-metal systems revealed that intricate interplay existed between coexisting HMs, which hindered the simultaneous removal effect. The coexistence of Cr6+ and Cd2+ decreased both removal efficiencies by 58.16 % and 14.06 % at high Cr6+ levels, respectively, while the coexistence of Cd2+ and Pb2+ resulted in a decrease in Cd2+ removal efficiency by 14.3 %. An in-depth characterization of the underlying adsorption mechanism was performed by using kinetic and isotherms models such as Pseudo-first-order, Pseudo-second-order, Langmuir and Freundlich, X-ray photoelectron spectroscopy (XPS) and transmission electron microscopy (TEM) analysis. Each HM exhibited a distinct adsorption mechanism. The primary removal processes for Cr6+ and Pb2+ involved adsorption, reduction, and precipitation, whereas Cd2+ was mainly removed by adsorption and precipitation. Eco-toxicity experiments revealed that nZVI-BC enhanced pak choi (Brassica rapa L.) seeds germination (13.32, 17.22, and 23.33 %) and vigor indexes (1.22, 1.44, and 1.15) under Cr6+, Pb2+, and Cd2+ contamination, respectively. Nevertheless, an observed shift in toxicity occurred when the composites dosage for Cr6+, Pb2+, and Cd2+ exceeded 2, 4, and 4 g L−1, respectively, thereby instigating adverse effects on the early stages of plant growth. This work elucidates the removal mechanism and intricate reactions between co-existing HMs, highlighting the potential of nZVI-BC as a remediation strategy for HMs contamination.